Sarcoidosis presenting as orbital pseudotumor - S. Kobak; A. Topaloglu; G. Öncel; A. Karaarslan (PAGEPress Publications, 2015)
Sarcoidosis is a systemic multiorgan disorder of unknown etiology characterized by a non-caseating granuloma reaction. Ocular involvement has been reported in 25-60% of the patients. Seven percent of the patients with sarcoidosis may first see an ophthalmologist due to ocular complaints. This report aims to present our diagnostic and treatment approach to a female patient with significant unilateral lacrimal gland swelling and musculoskeletal involvement, who was diagnosed with sarcoidosis on the basis of tests and histological studies.